2014
DOI: 10.5539/ies.v7n5p104
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Teaching Profession as a Career: Students’ Reasons

Abstract: The success of educational change inevitably depends on the quality and performance of teachers. Therefore, the importance of employing high quality teachers is crucial for educational systems. Choosing talented and committed brains to teaching career depends on making it an attractive profession. It is considered that there are some reasons why student teachers choose teaching as a career. Many studies reveal that while some students choose this profession with altruistic-intrinsic and extrinsic reasons, some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 51 publications
(50 reference statements)
8
38
0
9
Order By: Relevance
“…Descriptive analysis of the demographic data showed that most of the participants were from low and middle-income families, and majority of them were females, which suggested a positive relationship between gender and choosing teaching as a career. This result is consistent with the previous studies that have demonstrated that teaching is becoming an increasingly female-dominated profession (Azman, 2013;Balyer & Özcan, 2014;Low, Lim, Ch'ng, & Goh, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…Descriptive analysis of the demographic data showed that most of the participants were from low and middle-income families, and majority of them were females, which suggested a positive relationship between gender and choosing teaching as a career. This result is consistent with the previous studies that have demonstrated that teaching is becoming an increasingly female-dominated profession (Azman, 2013;Balyer & Özcan, 2014;Low, Lim, Ch'ng, & Goh, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…It is easier to meet the students' needs when they study in relatively low standard departments in which teaching profession is included. These results prove that teaching profession is for lower middle classes (Balyer & Özcan, 2014;Banks, 1995;Zeichner, 1996). Besides, the students who are coming from the crowded families choose teaching as a career just because of the extrinsic reasons.…”
Section: Discussionmentioning
confidence: 63%
“…In his multivariate analysis Yang (1981) found that father's education extended strong influence than the mother's upon the aspirations levels of the students A consistently relationship has been found between the family socio economic status and students' career choices (Yang, 1981;Elsworth et al, 1982). In their resaerch, conducted to 1400 teacher candiataes in different Turkish universities Balyer & Özcan, (2014) found that most of the students come from lower socio-economic families who live in villages and small towns. This result shows that low socio economic status families cannot provide better chances for their students to choose their careers.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there is congruence within each cohort's personal and professional values. Many of the values expressed by the pre-service teachers, along with the key responsibilities they felt teachers should uphold, reflect those found in past research; highlighting a belief in supporting, respecting, accepting, encouraging and positively influencing the range of students that will be in their classrooms (Bakar et al, 2014;Balyer & Ozcan, 2014;Dundar, 2014;. Reassuringly, the values preservice teachers listed as important to them personally and professionally are among those that are needed for inclusion (Booth, 2011) and quality teaching (Lovat, 2010) to prosper.…”
Section: Implications For Teacher Education Programsmentioning
confidence: 87%
“…A range of studies indicate that pre-service teachers and teachers do have a commitment to enhancing those values that align with inclusive education, such as making a positive difference to the lives of students, helping students to become more aware of their needs, abilities and goals, shaping and supporting students, and caring for students (Balyer & Ozcan, 2014;Manuel & Hughes, 2006;O'Sullivan, 2005). In Australia, Richardson and Watt (2006) surveyed 1653 pre-service teachers from three Australian universities to determine the factors that most influenced their choice of teaching as a profession.…”
Section: Values Of Pre-service Teachersmentioning
confidence: 99%